Typifications of the Linnaean name Equisetum hyemale and E. ×moorei (Equisetaceae) - Ferrer-Gallego, P. Pablo; Laguna, Emilio; Rosselló, Josep A. (Phytotaxa, 2017)
The lectotypes of the names Equisetum hyemale Linnaeus (1753: 1062) and E. ×moorei Newman (1854: 19) (Equisetaceae) are designated. Previously, a neotype for E. hyemale was selected by Hauke in 1962 from a specimen kept at LINN. However, this typification is rejected since there are two original elements that may contribute to a correct lectotypification of the name. Therefore this choice is ineffective and should be rejected. An illustration from Mattioli (1586) is designated as the lectotype. On the other hand, in order to avoid any ambiguity in the interpretation of the lectotype, an epitype is also selected. A lectotype for E. ×moorei, the putative hybrid between E. hyemale and E. ramosissimum Desfontaines (1799: 398–399) is designated on the basis of a specimen kept at DBN.